THE EFFECT OF WORK ENVIRONMENT, COMPENSATION AND CAREER DEVELOPMENT ON TURNOVER INTENTION OF GENERATION Z EMPLOYEES IN THE COMPANY X - Juliyanti, Indah; KorikaSwasti, Ika (PT Larva Wijaya Penerbit, 2025)
This study aims to determine the influence of the work environment, compensation, and career development on turnover intention among Generation Z employees in the company x. The method used was quantitative. Data collection was conducted using a questionnaire, with a Likert scale as the measurement scale. The sampling technique used was a saturated sample, consisting of all 50 Generation Z employees in the company x. Data were analyzed using PLS (Partial Least Squares). The results showed that the work environment had a negative and significant effect on turnover intention, career development had a negative and significant effect on turnover intention, and career development had no direct effect on turnover intention.